Dispersive slab waveguide modeling of discontinuities in ionosphere - Sengor, T (IEEE, 2003)
This work brings a suitable solution to the problems related to the interactions of electromagnetic waves with ionosphere by considering the ionosphere as involving several Drude type materials, which have specific configuration created with slab waveguide structures. The problem is solved by a computational technique developed as suitable to the problem explained here.
Keywords: Engineering; Remote Sensing